Strategies of Female Teaching Attending Physicians to Navigate Gender‐Based Challenges: An Exploratory Qualitative Study. Issue 8 (22nd July 2020) - Houchens, Nathan; Quinn, Martha; Harrod, Molly; Cronin, Daniel T; Hartley, Sarah; Saint, Sanjay
Abstract : BACKGROUND: Women in medicine experience discrimination, hostility, and unconscious bias frequently and with deleterious effects. While these gender‐based challenges are well described, strategies to navigate and respond to them are less understood. OBJECTIVE: To explore the lived experiences of female teaching attending physicians emphasizing strategies they use to mitigate gender‐based challenges in clinical environments. DESIGN: Multisite exploratory, qualitative study. SETTING: Inpatient general medicine teaching rounds in six geographically diverse US academic hospitals between April and August 2018. PARTICIPANTS: With use of a modified snowball sampling approach, female attendings and their learners were identified; six female attendings and their current (n = 24) and former (n = 17) learners agreed to participate. MEASUREMENTS: Perceptions of gender‐based challenges in clinical teaching environments and strategies with which to respond to these challenges were evaluated through semistructured in‐depth interviews, focus group discussions, and direct observations of rounds. Observations were documented using handwritten field notes. Interviews and focus groups were audio recorded and transcribed. All transcripts and field note data were analyzed using a content analysis approach. MAIN OUTCOMES: Attending experience levels ranged from 8 to 20 years (mean, 15.3 years). Attendings were diverse in terms of race/ethnicity. Strategic approaches to gender‐based challenges clustered around three themes: female attendings (1) actively position themselves as physician team leaders, (2) consciously work to manage gender‐based stereotypes and perceptions, and (3) intentionally identify and embrace their unique qualities. CONCLUSION: Female attendings manage their roles as women in medicine through specific strategies to both navigate complex gender dynamics and role model approaches for learners. Abstract :